Growth mindset in young people awaiting treatment in a paediatric mental health service: A mixed methods pilot of a digital single-session intervention. (April 2023) - Ching, Brian CF; Bennett, Sophie D; Morant, Nicola; Heyman, Isobel; Schleider, Jessica L; Fifield, Kate; Allen, Sophie; Shafran, Roz
Background: Wait times are significant in child mental health services but may offer opportunity to promote growth mindsets in young people with physical and mental health needs. A digital growth mindset single-session intervention is effective in young people, but its use in paediatric settings has not been examined. This mixed methods pilot aimed to assess the intervention's feasibility, acceptability, and impact in this population. Method: Patients aged 8–18 on waiting lists in a paediatric hospital's specialist mental health service were offered the intervention remotely. Treatment completion and retention rates, symptoms of depression and anxiety, perceived control, and personality mindset were assessed at baseline, post-treatment, and follow-ups. Semi-structured interviews to explore the intervention's acceptability were conducted post-treatment. Results: Twenty-five patients completed the intervention and 17 patients and three carers/parents were interviewed. Outcomes showed small to large improvements across time-points. Most patients reported finding the intervention enjoyable, accessible, and instilled a hope for change. They valued elements of the intervention but made suggestions for improvement. Conclusions: The digital growth mindset single-session intervention is feasible, acceptable, and potentially beneficial for young people with physical and mental health needs on waiting lists. Further research is warranted to examine its effectiveness and mechanism of change.